1993
DOI: 10.1159/000109516
|View full text |Cite
|
Sign up to set email alerts
|

Plasma 6-Hydroxymelatonin, 6-Sulfatoxymelatonin and Melatonin Kinetics after Melatonin Administration to Rats

Abstract: A specific, sensitive and reproducible high-performance liquid chromatographic (HPLC) method is described for the simultaneous measurement of 6-hydroxymelatonin and melatonin in rat plasma. Using this technique, a dose-dependent increase in 6-hydroxymelatonin concentration was observed 10 min after administration of different doses of melatonin. Plasma 6-hydroxymelatonin represented 1% of plasma melatonin, irrespective of the melatonin dose administered. After administration of 100 µg melatonin, 6-hydroxymelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 10 publications
3
15
0
Order By: Relevance
“…27 In brief, the analytical eluent consisted of 11.5% acetonitrile in a phosphate-citrate buffer (pH 7.4) and was delivered by a flow rate of 0.6 mL/min. Separation of the analytes were performed on a Hypersil ODS column (125 3 3 mm) with a particle size of 3 mm (MZ Analyventechnik, Mainz, Germany).…”
Section: Microsomal Incubations Extraction Procedure and High-perfomentioning
confidence: 99%
“…27 In brief, the analytical eluent consisted of 11.5% acetonitrile in a phosphate-citrate buffer (pH 7.4) and was delivered by a flow rate of 0.6 mL/min. Separation of the analytes were performed on a Hypersil ODS column (125 3 3 mm) with a particle size of 3 mm (MZ Analyventechnik, Mainz, Germany).…”
Section: Microsomal Incubations Extraction Procedure and High-perfomentioning
confidence: 99%
“…Previous studies have shown that the half-life of MEL in the blood circulation is 20 min and that it is rapidly converted to 6-hydroxymelatonin (6-OH MEL) in the liver (32). This major metabolite has 50 times less binding affinity for plasma membranes than MEL, but it possesses a free radical-scavenging indole ring and therefore could maintain antioxidant activity.…”
mentioning
confidence: 99%
“…It is possible that epileptic discharges might have appeared in all rats examined in this study if EEG recordings had been continued for a longer period. Since plasma melatonin level decreases rapidly, with a half-life of 22.5 min after injection (28), it is possible that chronic administration of melatonin may prevent the development of epilepsy.…”
Section: Discussionmentioning
confidence: 99%